L-U-band multiwavelength Brillouin-Raman fiber laser assisted by a broadband pump source - Al-Alimi, A. W.; Cholan, N. A.; Zainol Abidin, N. H.; Alresheedi, M. T.; Abas, A. F.; Ng, E. K.; Mahdi, M. A. (Springer, 2023)
We demonstrate the generation of multiple lasing wavelength in the L- and U-band from a Brillouin-Raman fiber laser. It was designed in a full-open cavity with a dispersion compensating fiber section as the nonlinear and Raman gain medium. A broadband source originated from the amplified spontaneous emission of an erbium-ytterbium-doped fiber amplifier was employed as the primary Raman pump. The proposed fiber laser system required a threshold power of 400 mW to initiate its first Brillouin Stokes line with 0.165 nm wavelength spacing. A total of 397 Stokes lines within 3-dB flatness of peak power extended from 1609.7 to 1675.0 nm corresponding to 65.3 nm wavelength range were obtained at the pump power of 850 mW. The utilization of broadband Raman pump source has enhanced the spectral bandwidth of multiwavelength generation. This approach is simple and can be employed to other wavelength ranges subject to the availability of the broadband pump source.